Microvascular responsiveness in obesity: implications for therapeutic intervention - Bagi, Zsolt (Blackwell Publishing Ltd, 2012)
Obesity has detrimental effects on the microcirculation. Functional changes in microvascular responsiveness may increase the risk of developing cardiovascular complications in obese patients. Emerging evidence indicates that selective therapeutic targeting of the microvessels may prevent life-threatening obesity-related vascular complications, such as ischaemic heart disease, heart failure and hypertension. It is also plausible that alterations in adipose tissue microcirculation contribute to the development of obesity. Therefore, targeting adipose tissue arterioles could represent a novel approach to reducing obesity. This review aims to examine recent studies that have been focused on vasomotor dysfunction of resistance arteries in obese humans and animal models of obesity. Particularly, findings in coronary resistance arteries are contrasted to those obtained in other vascular beds. We provide examples of therapeutic attempts, such as use of statins, ACE inhibitors and insulin sensitizers to prevent obesity-related microvascular complications. We further identify some of the important challenges and opportunities going forward. LINKED ARTICLES: This article is part of a themed section on Fat and Vascular Responsiveness. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2012.165.issue-3